2018
DOI: 10.1177/0306624x18784185
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Group Therapy Based on Schema-Focused Approach for Reducing Depression in Prisoners Living With HIV

Abstract: Depression is one the most common mental disorders in prisons. People living with HIV are more likely to develop psychological difficulties when compared with the general population. This study aims to determine the efficacy of cognitive group therapy based on schema-focused approach in reducing depression in prisoners living with HIV. The design of this study was between-groups (or "independent measures"). It was conducted with pretest, posttest, and waiting list control group. The research population compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Regardless of the type (i.e., coping improvement, mindfulness-based, schemafocused, and culturally tailored), PWH benefited from group therapy as they presented fewer depressive symptoms following the intervention period. Despite half the studies not requiring a depression criterion [24,28,29], short-term effects on depression were displayed across all the studies. One study found that depressive symptoms decreased over the 8-month follow-up period [24], and another found trends toward depressive symptoms decreasing at 12-month follow-up [27•].…”
Section: Group Therapy Interventionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Regardless of the type (i.e., coping improvement, mindfulness-based, schemafocused, and culturally tailored), PWH benefited from group therapy as they presented fewer depressive symptoms following the intervention period. Despite half the studies not requiring a depression criterion [24,28,29], short-term effects on depression were displayed across all the studies. One study found that depressive symptoms decreased over the 8-month follow-up period [24], and another found trends toward depressive symptoms decreasing at 12-month follow-up [27•].…”
Section: Group Therapy Interventionsmentioning
confidence: 98%
“…Adopting a distinct approach toward group interventions, Jalali et al [28] conducted a randomized controlled trial with 42 men with HIV in prison to test a schema-focused approach for reducing depression. Participants must have presented mild depressive symptoms or greater at baseline but could not have had a clinical depression diagnosis before their incarceration and HIV diagnosis.…”
Section: Group Therapy Interventionsmentioning
confidence: 99%
“…The study’s total sample size ranged from 32 to 1140, intervention sample sizes ranged from 19 to 578 and control group sample sizes ranged from 13 to 562. The majority of studies (n = 22, 73.33 %) reported on interventions for depression [33‐55]. Major depressive disorder was confirmed using diagnostic interviews such as SCID or MINI in three studies [34‐36].…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded in a study that schema therapy contributes to the improvement of cognitive emotion regulation strategies in patients with HIV (Farmani-Shahreza, Ghaedniay-jahromi, Mohammad-Taghi Nasab, Niknezhad & et al, 2017). A study was conducted on female prisoners who suffer from HIV and results showed that schema therapy-based cognitive therapy could reduce psychological, emotional, and depression problems (Jalali, Hasani, Hashemi, Kimiaei & Babaei, 2019). In another research, findings implied the positive effectiveness of schema therapy in reducing emotion dysregulation (Dadomo, Panzeri, Caponcello, Carmelita & Grecucci, 2018).…”
Section: Introductionmentioning
confidence: 99%